Relationship between management control systems and organizational change: Results of an exploratory study - NAFZAOUI , Mohammed Achraf; BELKINDOUSSI , Omar (Revue Internationale des Sciences de Gestion, 2024)
The objective of this study is to understand the relationship between management control systems (MCS) and organizational change as perceived and implemented by administrative staff within public healthcare organizations. After reviewing existing literature, the authors chose to adopt (Simons,1995) levers framework, with a particular focus on the two styles (interactive and diagnostic), resource-based view (RBV) (Barney, 1991), (Penrose, 1959), (Wernerfelt, 1984), and literature on organizational change. The authors’ methodology relies on qualitative analysis, primarily based on data collected through semi-structured interviews with hospital administrative staff (n=25). The results suggest that the interactive use of management control systems has a positive and significant impact on strategic flexibility, employee empowerment, and organizational learning. Furthermore, it has been confirmed that these three capabilities play a mediating role in the relationship between interactive use of MCS and organizational change. Conversely, no correlation was observed between diagnostic use of management control systems and organizational change through these three capabilities.